An assessment of non-governmental organizations’ roles in combating women/children trafficking in Vietnam - Ha, Nong Thi Thuy; Gan, Christopher; Kao, Christopher Betty (VNU JOURNAL OF ECONOMICS AND BUSINESS; Vol 27 No 5E, 2011)
Abstract. Confronting the problems of human trafficking, the government of Vietnam has made great efforts to combat it. In addition, Non non - G g overnmental O o rganizations (NGOs) and international organizations inVietnam have supported the country with anti-trafficking activities. They provide health care, accommodation and shelter, repatriation and reintegration programs. They have also implemented activities regarding prevention of victims, advocacy, community awareness raising and law enforcement. Despite of many successes, there remain numerous constraints NGOs confront in implementing the anti-trafficking programs effectively. This paper assesses the roles of NGOs in combating women/children trafficking inVietnam; investigates the roles of NGOs in combating women/children trafficking; assess the coordination mechanism between government and NGOs, and between NGOs and NGOs; and evaluate the effectiveness of NGOs in combating women/children trafficking. The problem could not be resolved in a couple of year due to complicated social, traditional and global issues. Moreover, loose border patrol and geographical difficulties make it easy for citizens to cross the borders thus the trafficking activities happen. Keywords: Human trafficking, Vietnam, Non non - G g overnmental O o rganizations.